2021
DOI: 10.3390/ijms221810087
|View full text |Cite
|
Sign up to set email alerts
|

Enjoy Carefully: The Multifaceted Role of Vitamin E in Neuro-Nutrition

Abstract: Vitamin E is often associated with health benefits, such as antioxidant, anti-inflammatory and cholesterol-lowering effects. These properties make its supplementation a suitable therapeutic approach in neurodegenerative disorders, for example, Alzheimer’s or Parkinson’s disease. However, trials evaluating the effects of vitamin E supplementation are inconsistent. In randomized controlled trials, the observed associations often cannot be substantiated. This could be due to the wide variety of study designs rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 121 publications
0
9
0
Order By: Relevance
“…Vitamin E shows several important properties including cholesterol-lowering, anti-inflammatory, and antioxidant properties along with anti-ferroptosis activity. It has also been indicated that vitamin E supplementation can be effective in the treatment of neurodegenerative diseases including PD and AD [ 202 ]. Antioxidant properties of vitamin E are closely associated with their anti-inflammatory effects, as OS is a part of inflammation [ 203 ].…”
Section: Targeting Ferroptosis and Inflammation In The Treatment Of N...mentioning
confidence: 99%
“…Vitamin E shows several important properties including cholesterol-lowering, anti-inflammatory, and antioxidant properties along with anti-ferroptosis activity. It has also been indicated that vitamin E supplementation can be effective in the treatment of neurodegenerative diseases including PD and AD [ 202 ]. Antioxidant properties of vitamin E are closely associated with their anti-inflammatory effects, as OS is a part of inflammation [ 203 ].…”
Section: Targeting Ferroptosis and Inflammation In The Treatment Of N...mentioning
confidence: 99%
“…Furthermore, vitamin E plays a key role in gene regulation in brain cells, and its deficiency can lead to a dysfunctional central nervous system. Studies have proven a positive impact on cognitive impairment diseases, such as Alzheimer’s disease, Parkinson’s disease, 30 and epilepsy. 31 Other dysfunctions, such as male 32 and female infertility; 33 osteoporosis; 34 and lifestyle diseases, such as diabetes mellitus, 35 have had a promising positive impact from vitamin E supplementation in some clinical trials.…”
Section: Tocochromanolsmentioning
confidence: 99%
“…The efficacy of vitamin E and its derivatives, such as Trolox, as a potential treatment intervention for AD has been tested in several randomized studies (Regner-Nelke et al, 2021). Trolox can also protect against neurotoxicity caused by Aβ and inhibit glycogen synthase kinase 3 (GSK 3), a protein in neurofibrillary tangle development (Muñoz et al, 2002;Radesäter et al, 2003).…”
Section: Therapeutic Potential In Alzheimer's Disease and Clinical Trialmentioning
confidence: 99%
“…Despite this, evidence for vitamin E's therapeutic effectiveness in the treatment of AD remains unclear. Despite strong evidence of increased ROS in AD etiology and lower circulating vitamin E levels, clinical trials examining vitamin E as a treatment have yet to show conclusive results (Regner-Nelke et al, 2021). When no clinical studies have been conducted with Trolox specifically for AD, studies have shown that a combination of donepezil and Trolox has been tested as multifunctional agents for AD.…”
Section: Therapeutic Potential In Alzheimer's Disease and Clinical Trialmentioning
confidence: 99%